Prevalence of habit of tobacco and its deleterious effects in general population of Jaipur District, Rajasthan - Vela Desai; Rajdeep Kaur Gill; Rajeev Sharma (Wolters Kluwer Medknow Publications, 2012)
Introduction: Usage of tobacco is prevalent worldwide in some or other form in all age groups. Smoking and tobacco use is a major public health issue in developing countries. As Rajasthan is a place with different cultural and traditional variations when compared with other parts of the world. To extract if the same diversity exists in the usage of tobacco in Jaipur district Rajasthan, this study was conducted as no similar studies have been done previously Materials and methods: A total of 552 patients who visited Outpatient Department of Jaipur Dental College, Jaipur, were studied. Complete information regarding presence of smoking and other forms of tobacco was recorded in case history proforma and any of tobacco-related oral lesions among these patients were examined. Results: In age group of <20 years, 109 males and 62 females gave history of habit of tobacco. A total of 164 males and 146 females were in the age group of 21 to 50 years, which made the highest total of 56.169o. Diagnosis included leukoplakia in 111 patients, lichenoid reaction (p-value > 0.05) in 12.84% subjects, oral cancer was reported in 33 patients (p-value = 0.001) whereas smoker's palate in 25 patients and OSMF being the most common. Awareness level about ill effects of tobacco was 51.10 %. Conclusion: High incidence of tobacco usage in smokeless form is seen in Jaipur population especially in adolescents. There were no significant findings found between males and females. Of all lesion examined, OSMF was found to be more prevalent. Therefore, it is important to take immediate steps to curb the habit.